Perubahan Makna dan Strategi Transkreasi dalam Penerjemahan Iklan Dove “Real Beauty”: Tinjauan Teori Skopos dan Dynamic Equivalence - Maulana, Muhammad Fanza (Program Studi Tadris Bahasa Indonesia, 2025)
This study aims to analyze the transcreation strategy and the shift in meaning in the translation of the Dove Real Beauty advertisement from English into Indonesian, using Skopos theory and Dynamic Equivalence as analytical approaches. In the context of advertising translation, literal translation often fails to effectively convey the intended message to the target audience due to cultural and social value differences. Therefore, transcreation serves as a crucial strategy that allows creative adaptation of the message without losing its core meaning.This research employs a descriptive qualitative approach with a comparative text analysis method. The primary data consist of two versions of Dove’s advertisement: the English version titled Let’s Break the Rules of Beauty and the Indonesian version titled Beragam Kecantikan, Satu Indonesia (“Diverse Beauty, One Indonesia”). The analysis focuses on both verbal and visual elements in the advertisements by examining shifts in narration, slogan, language style, and female visual representation. The findings show that transcreation is used to adapt the global advertising message to be culturally relevant for the Indonesian audience. Skopos theory helps explain how the communicative purpose of the advertisement is tailored to local values such as diversity and unity. Meanwhile, Dynamic Equivalence demonstrates that the emotional impact of the advertisement remains consistent despite changes in linguistic and visual forms. In conclusion, advertising translation requires a creative and adaptive approach to effectively bridge meaning across cultures.